Identification of Methane-producing Bacteria from Palm Oil Mill Sludge (POMS) with Solid Cud from Ruminant Stomach - Chan, CSW; Lau, S.; Husaini, A. A. S. A; Zulkharnain, A.; Kasing, Apun; Bilung, L. M; Vincent, M. (Hibiscus publisher, 2014)
Biological generation in anaerobic environments such as enteric fermentation and anaerobic waste treatment from agriculture sector are the major contributor of methane gas which has the potential as biogas. The aimed of this study was to identify methane-producing bacteria in anaerobic vessel which contained a mixture of Palm Oil Mill Sludge (POMS) and solid cud taken from the first compartment of cow’s stomach (1:2 and 2:1 ratio) as co-mixture. The comixture was incubated at 50 °C in a 2 L vessel with initial starter of 400 ml and sampling was conducted every 4 weeks interval during 12 weeks of incubation. For specific detection of methanogens, 16S rRNA-cloning analysis was carried out. Methanobrevibacter sp. and Methanosaeta sp. were confirmed to be presence within the 2:1 ratio of co-mixture while only Methanobrevibacter sp. was found in 1:2 ratio of co-mixture on both Week 0 and Week 4. No methanogens were detected for both co-mixtures on Week 8 and Week 12